Wspólny Rynek Południa (Mercosur) z perspektywy prawa międzynarodowego - Mik, Cezary (Kwartalnik Prawa Publicznego, 2017)
The Common Southern Market (Mercosur) is one of the younger and more important integration organizations of South America. From the point of view of international law, this is not a typical international organization, because although it has a treaty-based basis and its members are states, it performs primarily the integration function and not only intergovernmental cooperation, it has organs that are not typical for traditional international organizations, its law is a legal order that shows partially specific features, aiming for autonomy in relation to international law, although the sources of law are not self-executing in national orders, and the dispute resolution system is not exclusive. Mercosur has limited subjectivity of international law. It independently uses this subjectivity to a modest extent. In most cases, international agreements are concluded by Member States acting collectively as Merocsur. Intergovernmental mechanisms allow Member States to maintain a strong position and status of a sovereign state in the organization.